Reducing activity costs under Resource Consumption Accounting: An Applied Research in the MidlandRefineriesCompany-Al Daura Refine (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research aims to identify the importance of applying resource consumption accounting in the Iraqi industrial environment in general, and oil in particular, and its role in reducing the costs of activities by excluding and isolating idle energy costs, as the research problem represents that the company faces deficiencies and challenges in applying strategic cost tools. The research was based on The hypothesis that the application of resource consumption accounting will lead to the provision of appropriate information for the company through the allocation of costs properly by resource consumption accounting and then reduce the costs of activities. To prove the hypothesis of the research, the Light Derivatives Authority - Al-Dora Refinery in the Midland Refineries Company was selected as a sample for the research. The most important recommendations are the need for the company's management to adopt the process of spreading awareness and the philosophy of the popular culture of the concept of accounting for resource consumption to provide conviction and acceptance for its implementation by employees, as well as including comprehensive and adequate analysis of internal and external environmental factors in all activities of the company at the administrative and organizational levels.